1983
DOI: 10.1038/ki.1983.42
|View full text |Cite
|
Sign up to set email alerts
|

Renal disease profoundly alters cortical interstitial cell function

Abstract: Interstitial cells were cultured from explants of the unilaterally hydronephrotic, contralateral, and normal kidneys. Two types of cells were identified in culture, macrophages, and cells which were tentatively identified as fibroblasts. Cells grew at a significantly faster rate in hydronephrotic compared to contralateral or normal kidneys. Cells from the hydronephrotic kidney increased prostaglandin (PG)E2 production in response to bradykinin. Cells from contralateral and normal renal cortex did not increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…Contrary to Davis et al [35], who found a high proportion of macrophages in rabbit cell culture, these cells were not discernable in passage 2 cultures from rat kidneys. Primary renal cell suspensions contain macrophages which attach to culture dishes, but these cells do not grow in cell culture whereas other cells divide.…”
Section: Resultscontrasting
confidence: 51%
“…Contrary to Davis et al [35], who found a high proportion of macrophages in rabbit cell culture, these cells were not discernable in passage 2 cultures from rat kidneys. Primary renal cell suspensions contain macrophages which attach to culture dishes, but these cells do not grow in cell culture whereas other cells divide.…”
Section: Resultscontrasting
confidence: 51%
“…However, several lines of evidence obtained in studies with uterus, intestine, and kidney indicate that stromal or lamina propria elements, rather than epithelial cells, may be major PG producing cells (40)(41)(42) and that inflammatory cells specifically may be important contributors to tissue PG production. After the induction of hydronephrosis, renal PG production is markedly increased.…”
Section: Resultsmentioning
confidence: 99%
“…The cells displayed typical mor phological features of cultured fibroblasts. Be fore confluency, they were identical with the nonphagocytic cells obtained in tissue culture from explants of rabbit kidneys [20] (fig. 1).…”
Section: Discussionmentioning
confidence: 81%